Ketahanan Pangan Keluarga Orang Rimba Selatan Taman Nasional Bukit Dua Belas Jambi: Studi Mikroetnografi Keluarga Njalo Dalam Menghadapi Pandemik - Kristiawan John; Adi Prasetijo; Dwi Sutiningsih (Universitas Andalas, 2021)
The Orang Rimba are a hunting-gathering group that lives depending on the availability of the forest. Forests not only function as livelihoods but also have cultural significance as a resource for their cultural traditions. However, in the last few decades, forest conversion in Jambi province has increased. The increased function of forests in Jambi from forests as plantation areas, mining areas and industrial plantation forest areas has made the lives of the Orang Rimba as a hunting-gathering group increasingly threatened. Food security is a condition in which all people, at any time, have access both physically, socially, and economically to adequate, safe, and nutritious food which can meet food needs and food preferences for an active and healthy life. Through the micro ethnography approach, the purpose of this paper is to know and understand the phenomenon of food security from the perspective of the Orang Rimba as seen from its availability, adequacy, affordability, and security. Orang Rimba have food security by relying on food sources available in the forest. In a state of urgency they will return to the forest.